Beta-cyclodextrin modified mesoporous bioactive glass nanoparticles/silk fibroin hybrid nanofibers as an implantable estradiol delivery system for the potential treatment of osteoporosis. Issue 38 (26th September 2018) - Wang, Dong; Steffi, Chris; Wang, Zuyong; Kong, Chee Hoe; Lim, Poon Nian; Shi, Zhilong; Thian, Eng San; Wang, Wilson
Abstract : A hybrid nanofibers is produced for localized delivery and sustained release of estradiol in osteoporotic bone. Abstract : Osteoporosis, a systemic skeletal disease prevalent in elderly women, is associated with post-menopausal estrogen deficiency. Although systemic administration of exogenous estradiol (E2) reduced fragility fractures, the treatment has adverse effects. Localized delivery technologies of E2 could be utilized to circumvent the systemic adverse effects of systemic administration. In this study, a localized E2 delivery system is developed. Mesoporous bioactive glass nanoparticles (MBGNPs) with inherent osteogenic properties are modified with β-cyclodextrin (CD-MBGNPs) to enhance their affinity for E2. To ensure mechanical stability and integrity, E2 loaded CD-MBGNPs are further electrospun with silk fibroin (SF) to produce a nanofibrous mesh (E2@CD-MBGNPs/SF). The incorporation of MBGNPs in SF enhances in vitro apatite formation and sustains the constant release of E2. Moreover, osteoblast proliferation and differentiation markers such as alkaline phosphatase activity, collagen 1 and osteocalcin expression of MC3T3-E1 are augmented in CD-MBGNPs/SF and E2@CD-MBGNPs/SF as compared to SF nanofibers. On the other hand, osteoclast DNA, tartrate resistant acid phosphatase activity and multinucleated cell formation are reduced in E2@CD-MBGNPs/SF as compared to CD-MBGNPs/SF and SF. Hence the presence of CD-MBGNPs in SF stimulates osteoblast function whereas E2 incorporation in CD-MBGNPs/SF reduces osteoclast activity. This is the first report to develop CD-MBGNPs/SF as a localized delivery system for hydrophobic molecules such as estradiol to treat osteoporosis.